2012
DOI: 10.3126/hn.v11i1.7219
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Mechanisms in Agriculture for Climate Change in Nepal

Abstract: In Nepal, impacts of climate change can be observed in varying levels of climate that are prevalent in diversified topography and vegetation. Broadly speaking, there are impacts of climate change in the Terai lowlands, the mid-hill valleys and mountains, and in the high Himalayas. Nepal is a unique climatic laboratory for studying the impacts of climate change.Sixty-five percent of the Nepalese people engage in agriculture and more than 32% of Gross Domestic Product (GDP) comes from it. There are evidences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Climate change has been observed in Nepal in varying level of climates that are prevalent in diversified topography and vegetation (Paudel, 2010(Paudel, , 2012. There are impacts of climate changes in Terai, mid-hills and valley (subtropical region), and mountains and the Himalaya (temperate and tundra regions) of Nepal.…”
Section: Climate Change and Nepalmentioning
confidence: 99%
See 4 more Smart Citations
“…Climate change has been observed in Nepal in varying level of climates that are prevalent in diversified topography and vegetation (Paudel, 2010(Paudel, , 2012. There are impacts of climate changes in Terai, mid-hills and valley (subtropical region), and mountains and the Himalaya (temperate and tundra regions) of Nepal.…”
Section: Climate Change and Nepalmentioning
confidence: 99%
“…In agriculture, about 10% of agricultural land was left fallow due to rain deficit on the one hand, while on the other hand in the midwestern Terai faced heavy rain with floods, which reduced crop production by 30% (Regmi, 2007). Adverse effect of climate change could lead to the extinction of some indigenous crop varieties such as many aromatic rice varieties including Basmati rice, some local wheat, maize, and other agricultural crops as well (Paudel, 2012). It was also observed that a severe winter cold wave in Nepal in 1998 had negative impacts on agricultural productivity and showed a high percentage of yield reduction for potato (27.8%), leaf mustard (36.5%), mustard seed (11.2%), lentil (37.6%), and chickpea (38%) (NARC 1987(NARC /88 to 1997.…”
Section: Climate Change and Nepalmentioning
confidence: 99%
See 3 more Smart Citations